The pragmatics of pragmatic labelling for the observahumor.com platform - Ruiz Gurillo, Leonor (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Working with a pragmatic phenomenon such as humour is a complex task, dependent as it is on the discursive genre in which humour appears and on the conversational contract of the speaker-writer and listener-reader (Ruiz Gurillo, 2016). In this sense, a particular challenge for researchers of Spanish pragmatics is the relative dearth of recent linguistic corpora compiled using research- and methodologically-based data. This article outlines the need for pragmatic labelling to be applied to one specific humour corpus, the OBSERVAHUMOR.COM platform. Although the literature has repeatedly referred to humour markers as constituting clues to help addressees interpret humour (see, among others, Burger and van Mulken, 2017), a further group of elements, humour indicators, should also be recognised. These are common elements in the language, but which become humorous elements per se in a given context (Ruiz Gurillo, 2014; Timofeeva and Ruiz Gurillo, 2021). A review of the different humour markers and indicators that are seen to function in various humour corpora forms the basis for the current proposal, which aims to establish a system of pragmatic labelling, illustrated here using the various corpora that comprise the OBSERVAHUMOR.COM platform: CHILDHUM, VALESCO.HUMOR, ERASMUS.HUMOR, COLUMNAS.HUMOR, FEMMES.UP and BLOGS.HUMOR.
Keywords: humour marker; humour indicator; pragmatic labelling; corpus